Financing social insurance schemes for agricultural workers in the Middle East and North Africa - Lucas Sato; Nicole Figueiredo; Nourjelha Mohamed (International Policy Centre for Inclusive Growth (IPC-IG), 2022)
This Research Report, the second in the series "Expanding Social insurance for agricultural workers in Middle East and North Africa (MENA): identifying key constraints and discussing policy options", focuses on the financial barriers to expand social insurance for agricultural workers.
Keywords: 330; social insurance; financing social protection; agricultural workers; MENA